Agricultural Trade and Its Determinants: Evidence from Bounds Testing Approach for Turkey - Sertoglu, Kamil; Dogan, Nezahat (International Journal of Economics and Financial Issues, 2016)
This paper empirically analyses the long run relationship between agricultural trade performance and real exchange rate in Turkey by using quarterly data covering 1994:Q1-2012:Q3. The other factors that are expected to effect agricultural trade balance such as ratio of export and import prices of agricultural goods, producer prices, real income of the country are also added to the model. For this purpose, bounds test approach for co-integration and ARDL (Autoregressive Distributed Lag) method are used to show the existence of long-term relationship between agricultural trade balance and its determinants in Turkey. The results show that real exchange rate, real GDP, and agricultural producer prices are highly significant and have negative impact on determining agricultural trade balances in Turkey. Consequently, findings suggest that the policies or reforms that reducing producer prices and using new technologies to increase productivity may help to create trade surplus in agricultural trade of Turkey. Keywords: Agricultural Trade, Turkey, Bound Test Approach JEL Classifications: Q17, Q18, F14